(a cтеп 2 - а +а степ 4) : (-а степ 2)+ (а+ 3)(а -3) при а = -1

0 голосов
20 просмотров

(a cтеп 2 - а +а степ 4) : (-а степ 2)+ (а+ 3)(а -3) при а = -1


Алгебра (45 баллов) | 20 просмотров
Дан 1 ответ
0 голосов

Решите задачу:

\frac{a^2-a+a^4}{-a^2} +(a+3)(a-3)= \frac{a^2-a+a^4}{-a^2}+a^2-9= \frac{a(a-1+a^3)}{-a^2} +a^2-9 =
= \frac{a-1+a^3}{-a} +a^2-9=- \frac{a-1+a^3}{a} +a^2-9= \frac{-(a-1+a^3)+a^3-9a}{a}=
= \frac{-a+1-a^3+a^3-9a}{a}= \frac{-10a+1}{a}
a=-1, \frac{-10*(-1)+1}{-1} = \frac{10+1}{-1} = \frac{11}{-1} =-11
(26 баллов)